Determinants of Executive Employees' Stress at Indian Multinationals - Sivarethinamohan, Dr. R. (Prabandhan: Indian Journal of Management, 2008)
Living according to someone else's values is a highly reactive way of life and the reactive mode is extremely stressful. An inner conflict develops stress. Human beings tolerate certain levels of stress. Damage-psychological or physical -occurs when they are continually exposed to low or high levels of stress. The data were analyzed using a factor analysis-Principal Component model to see if the factors selected represent the dimensions of employees' stress. The employees under study, with a sample of 100 executives all over India, find it difficult to work and sleep with unsustainable load. They get stressed due to work related tasks. But they also have the unique ability to move, change or modify their relationship with stress situations. They get remedy with a Program of regular exercise for fitness, Effective time - management and trusting relationship with someone to share their problems and difficulties.